The role of APTX4870 peptide in reducing cellular inflammatory responses by inhibiting Mycobacterium tuberculosis-derived mycolic acid-induced cytotoxicity - Lin, Xue; Jia, Wei; Feng, Gangning; Su, Yajing; Kang, Yuting; Zhang, Chen; Liu, Wenmiao; Lu, Zhidong; Xue, Di (Frontiers in Microbiology, 2022)
Tuberculosis is a serious zoonotic disease caused by Mycobacterium tuberculosis (M.tb) and the M.tb complex. Mycolic acid is an extracellular carbohydrate polymer that is produced, secreted, and accumulated outside the cells of various M.tb strains. Mycobacterium-derived mycolic acid plays an important role in infection. However, reports on exploring drugs that inhibit mycolic acid-induced cytotoxicity are scant. This study aimed to focus on the function of the panned peptide in Mycobacterium-derived mycolic acid (M.tb-MA)-induced cell injury. We used phage display to isolate the heptapeptide (APTX4870) from different phage libraries (Ph.D-7, Ph.D-12, and Ph.D-C7C). The efficacy of APTX4870 against mycolic acid was demonstrated by evaluating clinical samples, and using in vitro and in vivo experiments. APTX4870 protected cells from apoptosis, promoted autophagy to inhibit inflammation, and reduced M.tb-MA-induced lung injury. These results indicate that this heptapeptide, which specifically targets M.tb-MA, may be used as a promising new therapeutic drug for M.tb infection.